POLITICAL SCIENCE FOR THEORY AND ACTION: BIOGRAPHICAL STUDY OF GIANFRANCO PASQUINO - Pinho de Abreu, Reginaldo (Revista Gênero e Interdisciplinaridade, 2024)
Given the undeniable contribution of Political Science to history, it is also necessary to understand the context in which its postulates were developed, as well as its most prominent figures. By exploring the main works and authors in the field, we can deepen our understanding of its content. From this perspective, this study aims to discuss the life and work of one of the most important international references in Political Science, the Italian scholar Gian Franco Pasquino, and the significant contributions he has made and continues to make to the field, with a focus on action-oriented approaches.